Self-Concept, Interest in Becoming a Teacher, Prerequisite Courses: What do the Most Determinant Factors in Microteaching Competencies of Prospective Teachers? - Tomo Djudin (STKIP Singkawang, 2019)
Self-concept, interest, learning motivation, and prerequisite knowledge potentially contributes to academic achievement. The aim of this study was to determine the relationship between self-concept, interest in becoming a teacher, academic achievement of prerequisite courses and prospective teachers’ competencies of microteaching. This correlational study involved 105 sixth semester students of science department in Education and Teacher Training Faculty (FKIP) of Pontianak, Tanjungpura University. The data collected by using the self- concept questionnaire and the questionnaire of interest in becoming a teacher. The achievement of prerequisite courses and the students’ competencies of microteaching taken from the academic subdivision of the faculty. The analysis found that self-concept, interest in becoming a teacher, and academic achievement in prerequisite courses associate significantly with prospective teachers’ competencies of microteaching (respectively rs = .35, rs = .38, and rs = .60, p < .05). In addition, coefficient of multiple correlation is also significant (R = .61, p < .05). It means that the relative contribution of predictor variables of this study on prospective teachers’ competencies of microteaching is 37.60% and the remaining 62.40% is determined by other uninvestigated variables. The study indicated that the prerequisite courses relate significantly with students’ ability to execute microteaching. Thus, an institution of teacher training should continually upgrade the quality of learning and instruction by providing the essential prerequisite content of courses the prospective teachers required.